Penerapan Model Pembelajaran Project Based Learning Berbantuan Media Video Untuk Meningkatkan Kreativitas Peserta Didik - Levina Herviani; Edi Fitriana Afriza; Gugum Gumilar (JURNAL ILMIAH NUSANTARA, 2024)
The low creative thinking ability of students in workshop and entrepreneurship subjects at SMA Negeri 2 Singaparna is caused by the use of learning models that are not in accordance with the material to be delivered. The purpose of this study was to determine the application of the project-based learning model assisted by video media to the creativity of students. This research uses a quantitative approach with the type of quasi experiment. The theory that underlies this research is the theory of learning constructivism developed by Jean Piaget. The population in this study were all students of class XII MIPA consisting of 4 classes with the number of students in each class was 36 people, the sample was taken using purposive sampling technique with the criteria that the class that obtained the lowest average pre-study score was used as the experimental class, while the class with the highest average pre-study score was used as the control class. The data collection technique used was to conduct pretests and posttests on the classes that had been sampled. The data that has been obtained is then processed by simple linear regression analysis, with the result that the application of the project-based learning model assisted by video media is able to improve the creative thinking ability of students compared to the control class using the conventional learning model after treatment.